A systematic review of the effect of sandplay therapy on social communication deficits in children with autism spectrum disorder - Yuxi, Ren; Shuqi, Jia; Cong, Liu; Shufan, Li; Yueyu, Long (Frontiers in Pediatrics, 2024)
Objective: To explore the efficacy of sandplay therapy in intervening social communication deficits in children with autism spectrum disorders (ASD), and whether this efficacy is influenced by the age of the children and the dosage of sandplay therapy intervention. Methods:Following the PICOS principle, randomized controlled trials (RCTs) related to sandplay therapy for social communication deficits in ASD children were retrieved from seven databases: PubMed, WOS, The Cochrane Library, Embase, CNKI, Wanfang, and VIP, from the inception of each database to November 10, 2023. Two experimenters independently conducted study screening and excluded studies with concomitant diseases, incomplete data, unextractable data, and non-randomized controlled trials. The PEDro scale was used for methodological quality assessment, and the GRADEprofiler method was employed to evaluate the quality of evidence. Stata17 software was used for meta-analysis, subgroup analysis, sensitivity analysis, and publication bias testing. The standardized mean difference (SMD) and 95% confidence interval (CI) were used as the effect statistics. Results: A total of 12 RCTs (791 cases) were included. Sandplay therapy had a positive impact on the social communication deficits of ASD children (SMD=-1.42, 95%CI [-1.79, -1.04], P＜0.001). Subgroup analysis revealed that sandplay therapy administered during the early school age (449 cases, SMD=-1.44, P＜0.05), for a duration of 22-28 weeks (208 cases, SMD=1.69, P＜ 0.05), and with a frequency of once per week (218 cases, SMD=-1.67, P＜0.05) was most effective in improving on social communication deficits of ASD children. Discussion: The quality of evidence in this study was rated as high, with good methodological quality, including 12 studies with better quality and no detection of bias risk. The study had high heterogeneity, which was attributed to the measurement tools and intervention duration through subgroup analysis, with no inconsistency found. Additionally, no downgrade factors related to imprecision, publication bias, or indirectness were identified. In conclusion, sandplay therapy is an effective measure to improve social communication deficits in children with ASD, and current evidence recommends early intervention using an individual sandplay therapy or integrated sandplay therapy intervention program once a week for 22 to 28 weeks, which can serve as evidence-based clinical guidance.